SMOKERS' RIGHTS IN THE WORKPLACE: AN EMPLOYEE GUIDE (Tufts Archival Research Center, 2007)
Employee Guide entitled, “Smoker’s Rights in the Workplace,” equipping the smoker to respond to a workplace smoking ban. Identifies courses of action for smokers to take against the actions taken by management or harassment by fellow coworkers. Adds information that should be included in letters written to Congressmen and newspapers expresses the discrimination that no smoking policies exhibit.